PENGUATAN MODERASI BERAGAMA MELALUI INTERFAITH DIALOGUE BERBASIS CANGKRUKAN DAN FILANTROPI PRODUKTIF DI DUSUN SODONG KABUPATEN PONOROGO - Agustia, Zennata; Tsuraya, Salma Fahriya; Miftahurrziki, Hanifah; Mayasari, Lutfiana Dwi (Kodifikasia, 2024)
Indonesia as a multi-racial, ethnic and religious country is ambivalent. On the one hand, it has a positive value because it shows Indonesia as a multicultural country, but on the other hand, this diversity also often triggers conflict. One of the government's efforts to minimize conflict due to religious diversity is by massively campaigning for the concept of religious moderation on various fronts. Both in educational institutions, government and political policies. The implementation of religious moderation at the village government level has been practiced by residents in Sodong Hamlet, Ponorogo Regency, East Java. Living with two religions in one village is acknowledged to often give rise to various clashes of interests. Therefore, this research aims to explore the strategies implemented by the people of Sodong Hamlet, Ponorogo Regency to internalize the value of religious moderation as an effort to foster peace between Buddhists and Muslims in the Hamlet. Through qualitative researce and data mining in the form of interviews, this research produces two conclusions; First, strengthening the value of religious moderation in Sodong Hamlet, Ponorogo Regency is carried out through Cangkrukan-Based Interfaith Dialogue. This program has proven successful in reducing the conflicting interests of the two religions. Second, strengthening religious moderation is carried out through productive philanthropic activities. Indirectly, this philanthropy program has opened a space for dialogue between Muslims and Buddhists. MSME actors from both religions can also understand digital media and halal criteria for food products. So that it can create benefits and social justice in the Sodong Hamlet community